Interní komunikace ve vybrané společnosti - Žebra, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Cílem této diplomové práce je analýza aktuálního stavu interní komunikace ve vybraném podniku, identifikace a posouzení neefektivních prvků interní komunikace napříč společností a následný návrh vhodných řešení, které by vedly ke zlepšení interní komunikace. Na základě teoretických východisek, rozhovorů a dotazníků svybranými zaměstnanci podniku jsou zvolena opatření vedoucí ke zlepšení informovanosti a motivace zaměstnanců. Tato opatření mají vdaném podniku kladný vliv na pracovní atmosféru i práci samotnou.

The aim of this thesis is to analyze the current state of internal communication in the selected company, identify and assess ineffective elements of internal communication across the company, and then propose appropriate solutions that would lead to the improvement of internal communication. On the basis of theoretical starting points, interviews and questionnaires with selected employees of the company, measures leading to the improvement of information and motivation of employees are chosen.These measures have a positive effect on the working atmosphere and the work itself in the given company.
Internal Communication in a Selected Company
Keywords: interní komunikace; komunikační procesy; efektivita; problémy vinterní komunikaci; internal communication; communication processes; effectivity; internal communication problems